Optimizing financial management and reporting to increase accountability and transparency in Islamic boarding schools‎ - Zahirah, Sayyidah Yasmin; Suhaedi, Wirawan (Universitas Islam Indonesia, 2025)
IntroductionIslamic boarding schools, known as pesantren, play a pivotal role in religious and educational development across Indonesia. However, as their institutional complexity increases, so does the demand for improved financial accountability and transparency. While prior research has acknowledged the significance of ethical governance in faith-based institutions, there remains limited empirical exploration of how Islamic values are operationalized within pesantren financial management.ObjectivesThis study investigates how pesantren optimize financial governance and reporting mechanisms by integrating spiritual principles and centralized institutional practices to enhance accountability and transparency.MethodUsing a qualitative, phenomenological research design, the study was conducted at three pesantren in Mataram City, West Nusa Tenggara. Data collection involved in-depth interviews with key administrators, direct observations, and financial document analysis. Thematic analysis was used to interpret the data and identify core patterns of governance.ResultsThe findings reveal that financial accountability in pesantren is rooted in Islamic spiritual values such as amanah (trustworthiness), siddiq (honesty), barakah (blessing), and husnudzon (positive presumption). These values shape ethical conduct and foster internal trust among stakeholders. Centralized financial management systems, complemented by informal communication practices, support transparency and efficient resource allocation. However, challenges such as limited technological infrastructure and reduced local autonomy remain.ImplicationsThe study suggests that effective financial accountability in pesantren can be achieved through a culturally embedded approach that aligns spiritual values with structured governance. This alignment strengthens institutional credibility and supports sustainable development.Originality/NoveltyThis research contributes to the academic discourse by presenting a faith-based financial governance model rooted in Islamic ethics. It offers practical insights for educational institutions seeking to harmonize religious identity with professional accountability standards.